Collateral ligament reconstruction in two horses following traumatic avulsion fracture using a knotless suture anchor construct. (11th November 2016) - Bell, C.; Torske, K.; Lobb, B.
Summary: This case report describes a technique for repair of medial collateral ligament avulsions in two horses. Both horses sustained traumatic injuries resulting in avulsion fractures at the origin of their medial tarsal and carpal collateral ligaments. This report describes the use of a knotless suture anchor to mechanically reconstruct medial collateral ligament avulsion injuries in two horses. The first horse, a 9‐year‐old Hannovarian Warmblood gelding presented for an acute nonweightbearing lameness in the right hindlimb. The injury was localised to the medial malleolus of the tibia and an avulsion fracture of the origin of the short medial collateral ligament of the tibiotarsal joint with disruption of the ligament was found on radiographs and ultrasound. The horse was taken to surgery and a reconstruction of the short medial collateral ligament was performed with a modified single row construct using a biocompatible, multistrand, long chain ultra‐high molecular weight polyethylene braided composite suture tape (2 mm Fibertape) and a single knotless suture anchor (5.5 × 19.1 mm PEEK SwivelLock C). The second horse, a 5‐year‐old Thoroughbred gelding presented for an acute nonweightbearing lameness in the left forelimb. The injury was localised to the medial styloid process of the radius and an avulsion fracture of the origin of the medial collateral ligament of the antebrachial carpal joint was found on radiographs and ultrasound. The horse was taken to surgery and a similar reconstruction procedure was performed to the collateral ligament. Both horses were recovered in a Robert Jones bandage without the use of casts or splints and recovered without incident. Both horses are sound and returned to previous level of athletic performance at 18 months and 8 months, respectively.